2010
DOI: 10.1007/s10694-010-0166-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Different Temperature Sensors in Standard Fire Resistance Test Furnaces

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The shielded thermocouples has slow temperature response time at the first 10 minutes of fire test, although the plate thermocouples has faster response time, but they have a short life span [17]. The criteria for acceptability shall be individually applied to all design temperatures included in the scope of the assessment in 50 °C steps, starting at 50 °C below the minimum temperature within the scope or 350 °C, whichever is the higher, up to the maximum temperature within the scope.…”
Section: Test Methodsmentioning
confidence: 99%
“…The shielded thermocouples has slow temperature response time at the first 10 minutes of fire test, although the plate thermocouples has faster response time, but they have a short life span [17]. The criteria for acceptability shall be individually applied to all design temperatures included in the scope of the assessment in 50 °C steps, starting at 50 °C below the minimum temperature within the scope or 350 °C, whichever is the higher, up to the maximum temperature within the scope.…”
Section: Test Methodsmentioning
confidence: 99%
“…The furnace temperature of the ASTM E119 fire test is controlled by shielded thermocouples, 4 while the furnace temperature of the ISO 834 fire test is controlled by plate thermometers 5 . The difference in the response time of the sensors results in higher temperatures and incident heat flux during the ASTM E119 fire test during the first 10 min; however, the differences in temperature become negligible after 10 minutes 18 . Consequently, the charring rates of timber exposed to a particular standard fire curve can be compared with the charring rate of timber exposed to other standard fire curves, as well as to the constant charring rates specified in Eurocode 5 2…”
Section: Timber Fire Tests From the Literaturementioning
confidence: 99%
“…The temperature data is obtained from an experimental work by Sultan et al [12]. The temperature profiles at the front and backside of the DFT are shown in Fig.…”
Section: Dft Field Data Analysismentioning
confidence: 99%
“…Lam and Weckman [11] examined the steady state response of four heat flux gauges including DFTs under various radiative and convective conditions and compared the results. In another study, Sultan [12] investigated the performance of six different temperature sensors in fire resistance test. The result showed that all the sensors yield similar results after approximately 10 min.…”
Section: Introductionmentioning
confidence: 99%